The Impact of Electricity Price on Economic Growth in South Africa - Khobai, Hlalefang Bernedict; Mugano, Gift; Le Roux, Pierre (International Journal of Energy Economics and Policy, 2017)
This study explores the relationship between electricity prices and economic growth in South Africa within a multivariate framework over the period 1985-2014. The autoregressive distributed lag (ARDL) bounds test is implemented to determine long run relationship among the variables. The findings of the ARDL model suggest that there is a long run relationship between electricity supply, economic growth, electricity prices, trade openness, employment and capital. Specifically, the empirical findings reveal that electricity prices negatively affect economic growth while electricity supply, trade openness, capital and employment have a positive impact on economic growth. These findings bring a fresh perspective for creating electricity policies that will enhance economic growth in South Africa. Keywords: Economic growth, electricity prices, South Africa JEL Classifications: O13, O4, Q43